A trend of osteocalcin in diabetes mellitus research: bibliometric and visualization analysis - Liu, Zixu; Mao, Yuchen; Yang, Kangping; Wang, Shukai; Zou, Fang (Frontiers in Endocrinology, 2025)
BackgroundOsteocalcin has attracted attention for its potential role in diabetes management. However, there has been no bibliometric assessment of scientific progress in this field.MethodsWe analysed 1680 articles retrieved from the Web of Science Core Collection (WoSCC) between 1 January 1986 and 10 May 2024 using various online tools. ResultThese papers accumulated 42,714 citations,with an average of 25.43 citations per paper. Publication output increased sharply from 1991 onwards. The United States and China are at the forefront of this research area.DiscussionThe keywords were grouped into four clusters: ‘Differential and functional osteocalcin genes’, ‘Differential expression of osteocalcin genes in relation to diabetes mellitus’, ‘Role of osteocalcin in the assessment of osteoporosis and diabetes mellitus’, and ‘Indirect involvement of osteocalcin in metabolic processes’. Analysis using the VoS viewer suggests a shift in research focus towards the correlation between osteocalcin levels and diabetic complications, the clinical efficacy of therapeutic agents or vitamins in the treatment of osteoporosis in diabetic patients, and the mechanisms by which osteocalcin modulates insulin action. The proposed focus areas are “osteocalcin genes”, “insulin regulation and osteoporosis “, “different populations”, “diabetes-related complications” and “type 2 diabetes mellitus”,“effect of osteocalcin expression on insulin sensitivity as well as secretion”,“osteocalcin expression in different populations of diabetic patients and treatment-related studies”.